Valorização de resíduos alimentares para a produção de biogás: desafios e oportunidades - Migliati, Caio Lobo (Universidade Federal de São Carlos, 2021)
In view of climate change aggravated by the use of fossil fuels, there is a need for solutions to reduce their use in order to help reduce greenhouse gases (GHG). Allied to this fact, food waste is discarded in large amounts causing severe environmental pollution in many countries. Among the different possible treatment routes, the anaerobic digestion (AD) of food residues for the production of biogas is a proven and effective solution for the treatment and recovery of these residues. Within this context, the objective of this work is to carry out an analysis of scientific publications, presenting relevant works and detailing the most important parameters for the production of biogas from food waste, understanding the broader global contours of ongoing scientific and technological research. In addition, a case study of the biogas plant of the Institute of Energy and Environment (IEE) at USP was carried out in order to demonstrate the feasibility of this process. For this, a detailed analysis of scientific data was performed using the database at Web of Science and Google Scholar, and Google Scholar (GA). Among the 677 studies found, there is a large presence of China conducting research and the growing interest in the subject, mainly related to solutions to climate change. Furthermore, the most relevant studies selected by the GA show the predominance of mesophilic batch systems, with mostly dry anaerobic digestion. The biogas plant demonstrated the feasibility of producing methane on an industrial scale, with methane content between 60-65% and cogeneration of 53.57 kWh per day of energy and a total of 152 hours in operation.
Recovering food waste for biogas production: challenges and opportunities
Keywords: Digestão anaeróbia; Co-digestão anaeróbia; Resíduos de alimentos; Biogás; ENGENHARIAS::ENGENHARIA QUIMICA